2021
DOI: 10.1016/j.rbmo.2021.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and their cargo are important regulators of cell function in endometriosis

Abstract: Long non-coding RNA, miRNA and proteins in exosomes isolated from the serum and peritoneal fluid of women with endometriosis are differentially expressed compared to controls. Experimental evidence demonstrates that exosome content modulates migration, invasion, angiogenesis and inflammation, central processes in endometriosis. It is suggested that exosomes and their content are important regulators in the pathophysiology of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…In addition, exosomes from endometriosis were reported to promote the phenotype of macrophages into MII polarization, and weaken the phagocytosis of macrophages in vivo and in vitro . Therefore, anti-exocrine therapy for patients with endometriosis seemed to significantly promote the recruitment of macrophages to ectopic lesions, reduce the proportion of MII-type phagocytes, and ultimately enhance the phagocytosis of macrophages to ectopic endometrial cells ( 40 , 41 ).…”
Section: Immunotherapy Of Endometriosismentioning
confidence: 99%
“…In addition, exosomes from endometriosis were reported to promote the phenotype of macrophages into MII polarization, and weaken the phagocytosis of macrophages in vivo and in vitro . Therefore, anti-exocrine therapy for patients with endometriosis seemed to significantly promote the recruitment of macrophages to ectopic lesions, reduce the proportion of MII-type phagocytes, and ultimately enhance the phagocytosis of macrophages to ectopic endometrial cells ( 40 , 41 ).…”
Section: Immunotherapy Of Endometriosismentioning
confidence: 99%
“…sEVs are functionally relevant to the pathophysiology of EMS [ 181 ], as sEV levels in the peritoneal fluid (PF) change according to the illness stage and cycle phase [ 182 ]. Five proteins are unique in EMS: (fragments of) peroxiredoxin-1 (PRDX1), annexin A2 (ANXA2), histone H2A type 2-C, inter-α-trypsin inhibitor heavy chain H4 (ITIH4), and tubulin a-chain.…”
Section: Sev and Emsmentioning
confidence: 99%
“…For instance, in complex regional pain syndrome (CRPS) patients Exo carry large amounts of miR-338-5p, indicating pathological conditions ( Kowalski et al, 2022 ). It was suggested that exosomal miR-338-5p could modulate NP after spinal cord injury via the regulation of apoptosis and neuroinflammation ( Freger et al, 2021 ). Molecular analyses have revealed a close relationship between exosomal miRNA and the production of pro-inflammatory cytokines such as IL-6 in response to pathological conditions ( Orlova et al, 2011 ).…”
Section: Exo Biogenesismentioning
confidence: 99%